The economic impact of Trans-Pacific partnership: What have we learned from CGE simulation? - John P. Gilbert; Taiji Furusawa; Robert D. J. Scollay (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2016)
The Trans-Pacific-Partnership (TPP) trade agreement, if successfully implemented, will liberalize trade between the US, Japan and ten other Asia-Pacific economies, making it one of the largest regional agreements ever seen. The prospect of a comprehensive trade agreement spanning the Pacific raises a number of important quantitative questions. One of the most widely used techniques for evaluating the economic impact of regional trading agreements is numerical simulation with computable general equilibrium, or CGE, models. There have now been a large number of papers written that use CGE methods to analyze the potential economic impact of the TPP agreement under varying theoretical and policy assumptions. In this paper we provide a synthesis of the key results that have emerged from the literature, and discuss some new simulation results of our own.
Keywords: F15; F17; C68; 330; Asia-Pacific; Regional Trade; TPP; CGE